Theory of Meaning Change in the Procedural Text Material - Roni Nugraha Syafroni (International Islamic Schools Alliance, 2021)
The background of this research is because students often confide in the researcher. They want material that is contemporary, contextual, nor merely textual. Therefore, the researcher took one of the materials about the procedural text combined with the theory of meaning change. The procedural text that the researcher used was a text about how to make crafts out of paper. The purpose of this study was to determine the benefits of the theory of meaning change in the procedural text material for class VII students. The method that researcher used in this research is descriptive analysis. The researcher took the theory of meaning change literature by Abdul Chaer. The results of this study indicate that theory of meaning change is beneficial when it is translated into procedural text material. Last, the conclusion of this research shows that theory of meaning change is beneficial when combined with procedural text material.